Investigation of Ldb19/Art1 localization and function at the late Golgi. - Jorge Y Martínez-Márquez; Mara C Duncan (PLoS ONE, 2018)
The arrestin-related family of proteins (ARTs) are potent regulators of membrane traffic at multiple cellular locations in the yeast Saccharomyces cerevisiae. Several ARTs act at multiple locations, suggesting that ARTs with well-established functions at one location may have additional, as of yet, uncharacterized roles at other locations in the cell. To more fully understand the spectrum of cellular functions regulated by ART proteins, we explored the localization and function of Ldb19/Art1, which has previously been shown to function at the plasma membrane, yet is reported to localize to the trans-Golgi network (TGN). We report that the C-terminal fusion of Ldb19 with GFP is functional and, as previously reported, localizes to the TGN. We further establish that Ldb19 associates with late stages of TGN maturation that are enriched in the clathrin adaptor protein complex-1 (AP-1). Additionally, we present genetic interaction assays that suggest Ldb19 acts at the late TGN in a mechanism related to that of AP-1. However, Ldb19 and AP-1 have dissimilar phenotypes in a subset of assays of membrane traffic, suggesting Ldb19 functions at the TGN are distinct from those of AP-1. Together these results indicate Ldb19 functions at the TGN, in addition to its well-established role in endocytosis.